Baulks, cultural heritage elements as ecological corridors in some traditional Romanian landscapes - IVAȘCU, Cosmin; RÁKOSY, László (Studia Universitatis Babeș-Bolyai Biologia, 2015)
The key objective of the current study is to make a general analysis about baulks, one of the structural elements that define a natural – cultural landscape, and that can be considered in a way “elusive”. Baulk can be defined as a narrow stripe of land acting as a border between two agricultural fields that are used in a rather traditional manner. They have a important role in the traditional rural communities, marking private properties, and there are special rules for the management of these structures. Within the landscape, baulks work as ecological corridors, linking the various natural and anthropic habitats. The interconnectivity of the different habitats and the maintenance of a high degree of biodiversity is practically assured, in the landscapes where these structures have been conserved. We especially focused on the baulks found in Banat, Maramureș and for other regions we used data from references.